Some aspects of the legal mechanism of ensuring of human rights and freedoms by bodies of the National Police of Ukraine - Толкачова, Ірина Анатоліївна; Полінська, Дар`я Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Peculiarities of activity of bodies of the National Police of Ukraine are considered in the article. Legal mechanism of ensuring of human rights and freedoms by bodies of the National Police of Ukraine is researched. Reasons which influence on the effectiveness of their activity are analysed.